Prevalence of cryptogenic transaminitis in the Leeds coeliac cohort. (13th March 2011) - Sainsbury, A; Fitzgerald, T; Davies, H; Howdle, P D; Everett, S M; Jennings, J S
Abstract : Introduction: Coeliac disease may be associated with a number of liver diseases. These include primary biliary cirrhosis, primary sclerosing cholangitis1 and elevated transaminases.2 We aimed to identify patients with coeliac disease and abnormal liver function tests. Methods: A database of patients with coeliac disease was established in Leeds in 2001. We retrospectively analysed this database. We searched our coeliac database to identify those with liver function test data. Results: A total of 537 individuals were recorded on the database. Overall 29% male, 71% female, mean age at diagnosis 43 years (range 0–88 years). Initial duodenal biopsy by Marsh grade: 0 18.9%, I 9.7%, II 31.2%, III 22.5% and IV 17.7%. There was a family history of coeliac disease (1st degree relative) in 12.7%. Selective IgA deficiency occurred in 1.7%. Data on ALT were available in 219 individuals. ALT was elevated in 11.9% (range 40–147 IU/l). 85% of these individuals were female. No association was found with alcohol consumption (mean 2.7 IU/week), weight (mean 67.8 kg), or compliance with a gluten-free diet. One individual had autoimmune thyroid disease, two weakly positive ANA and one was HIV positive. Data on ALP were available in 251 individuals. ALP was elevated in 5.2% (range 304–916 IU/l). Two individuals were ANA positive. No patient underwent liver biopsy. Conclusion: 11.9% of the population had elevated trasaminases. None of these had impaired liver function or established liver disease. The data is open to bias by the lack of liver histology and incomplete drug histories. Nevertheless, it supports the proposition that coeliac disease can be a potential cause of a cryptogenic transaminitis.